Genotype Environmental Interaction between Stress Thermic and milk production in Holstein cows in Lima region Peru - Menendez-Buxadera, Alberto (2023)
A total of 352596 results of the test day milk controls (TD), as well as the climatic variables of Temperature and Relative Humidity combined in an index known as ITH, carried out in 5 stables in the Lima region, between January 2006 and December 2018, were available for this study. This database was represented by the TD of 11876 Holstein daughters of 8439 dams and 321 sires and was studied by different random regression models with the objective to estimating the genetic relationships between TD and ITH as an indicator of heat stress (HS). The results indicated that heritability (h2 ), along the ITH scale shows a slightly upward trend (h2 = 0.113±0.01 to 0.187±0.02) until reaching its highest values in the so-called thermal stress zone (ITH>=68 to ITH=77). The genetic correlations (rg) were close to the unit between adjacent or very close ITH levels and decreased as the differences between the HS intensity measured by the ITH increased, reaching results between rg = 0.562±0.09 to 0.582±0.12 between the coldest area (ITH< = 61) and the hottest (ITH > = 71). The correlations between the estimated Breeding Value (BV) in both zones was 0.607 and only 262 of the top 600 animals selected were better in both zones. These responses indicate that the results of TD should not be considered as an expression of the same trait throughout the trajectory of ITH, in other words there is environmental genotype interaction. An index was made based on all the estimates of the BV throughout ITH that allowed to identify not only the existence of genetic variation in ST but also variations in the way animals responded to the different levels of ITH.